ANALYSIS AND MUTUAL IMPACT OF DIGITAL SERVICES QUALITY ELEMENTS - Momčilović, Oliver; Brzaković, Aleksandar; Brzaković, Stefan (Journal of process management and new technologies, 2022)
If there is a wish to attract new users and keep the existing stay, it is necessary to analyze the mutual impact of the elements on digital service quality. To date, numerous authors have conducted various empirical research studies. This study deals with the interstitial influences including reliability, responsiveness, and empathy. This research study has gone a step forward. It is aimed at determining how reliability and responsiveness, both individually and taken together, affect empathy in the Republic of Serbia on a projected sample of 458 small and medium enterprises, namely the manufacturing, service, and ICT activities. On the applied theoretical model, empirical research was conducted: descriptive statistics, correlation analysis and regression analysis, the impact of the independent elements on the dependent element. This research study is intended to help to understand the interdependence and degree of the influence present between said elements; this can provide help to SME owners and their managers with respect to the development of marketing strategies and good business practices in the digital age.
Keywords: digital services; reliability; responsiveness; empathy; correlation; regression; service quality